The essential controller an introduction to what every financial manager must know - Bragg, Steven M.; Bragg, Steven M.; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2012)
"This book is designed to give the new controller a firm foundation in the concepts of managing the accounting department, locating GAAP information, analyzing and knowing what to do with key accounting information, and setting up controls systems that reduce a company's risk of loss. These core areas are essentials to a controller's success. New to this edition will be a discussion of finance strategy; introduction of the accounting standards codification, update of the taxation strategy; and a new controller checklist will be added as an appendix"--
Rev. ed. of: Controller's guide. c2005.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Controllership; Chief financial officers; Corporations -- Accounting; Corporations -- Finance; Electronic books